Răspunsuri

2014-05-20T19:05:00+03:00
Chiar nu stiu !!!!!!!!!!!!!!!!!!!!!!!! !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!! !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!! !!!!!!!!!!!!!!!!!!!!!!!! !!!!!!!!!!!!!!!!!!!!! !!!!!!!!!!!!!!!! !!!!!!!!!!!! !!!!!!!!!!!!!! !!!!!!!!!!! !
Cel mai inteligent răspuns!
2014-05-20T19:23:40+03:00
A = 2√12 + 2√48 =2√4*3 + 2√16*3 = 4√3 + 8√3 = 12√3

b = 3√192 - 4√75 = 3√64*3 - 4√25*3 = 24√3 -20√3 = 4√3

a - 2ab/(a + b) = 12√3 - (2 * 12√3 * 4√3 )/(12√3 + 4√3) = 12√3 - (2*12*4*3)/(16√3) =
= 12√3 -  288 / 16√3 = 12√3 - 18/√3  aducem la acelasi numitor care este √3

(12√3 * √3 - 18)/√3 = (36 - 18)/√3 = 18 / √3    amplificam cu √3 sa scapam de √ la numitor

(18√3)/3 = 6√3



1 5 1